Faktor-faktor yang Berhubungan dengan Kejadian Kurang Energi Kronik (KEK) pada Ibu Hamil di Puskesmas Karang Mukti Tahun 2024 - sunarmi, sunarmi; Aisyah, Siti; Sari, Intant (NHM PRESS, 2025)
Chronic Energy Deficiency (CED) is a condition in which pregnant women suffer from prolonged (chronic) food deficiency, leading to various health disturbances during pregnancy. This study aims to determine the relationship between knowledge, parity, and attitude with the incidence of Chronic Energy Deficiency (CED) in pregnant women at Karang Mukti Health Center, Musi Banyuasin in 2024. The research method used was an analytic survey with a case-control approach. The population of this study comprised 150 respondents, and the sample size was 54 pregnant women who visited Karang Mukti Health Center during the study period. The data type used in this research was primary data. The statistical test employed was the chi-square test. The results of the statistical analysis showed a significant relationship between knowledge and the incidence of Chronic Energy Deficiency, with a bivariate analysis yielding a chi-square test result of P value (0.02) ≤ α (0.05). Similarly, a significant relationship was found between parity and the incidence of Chronic Energy Deficiency, with a P value (0.01) ≤ α (0.05), and between attitude and the incidence of Chronic Energy Deficiency, with a P value (0.02) ≤ α (0.05). The findings of this study are expected to contribute to references, insights, and knowledge related to chronic energy deficiency during pregnancy.